Ethnic and gender differences in financial management among college students - Falahati, Leila; Babaei, Hamidreza; Paim, Laily (Marsland Press, 2011)
The paper aims to examine ethnic and gender differences in financial management among college students. Using the stratified sampling method, 2,340 college students from six public and five private colleges were studied. The findings indicate gender differences in financial management, in which female students performed greater financial management than male students. The results revealed significant ethnic differences in financial management, in which Malay students performed greater financial management than Chinese and Indian students.